SYMPTOMS, COMPLICATIONS, AND PREVENTION OF THE GENETIC DISEASE XERODERMA PIGMENTOSUM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article is about what xeroderma pigmentosum is, its symptoms, treatment, and prevention. Early detection of this disease can protect you from skin cancer. Xeroderma pigmentosum (XP) is a rare genetic disease. It causes hypersensitivity to ultraviolet (UV) light, eye problems, and neurological symptoms. Xeroderma pigmentosum is caused by a gene change (mutation) inherited from your parents. There is no cure for XP, but treatment can reduce the risk of skin cancer and other complications.